Functional Ability and Risk of Fall among Older Adults in Pokhara - Adhikari, Sangita; KC, Takma; Shrestha, Nisha (Journal of Nursing and Health Sciences Nepal, 2025)
Introduction: Risk of fall is threat to the older adults with limited mobility and capabilities, and can reduce their ability to remain independent, decrease their well-being and lower quality of life. The objective of the study was to assess the functional ability and risk of fall among older adults in Pokhara. Methods: A quantitative, cross-sectional, descriptive research design was used to conduct this study in all geriatric homes of Pokhara. The study population comprised older adults aged 60 years and above residing in different geriatric homes in Pokhara. Probability sampling was employed to collect data from 112 older adults between 14 August and 10 September 2022. Data were collected by the researcher using a structured interview schedule and an observation checklist. Functional ability was measured using the standardized tool, the Katz Index of Independence in Activities of Daily Living. Risk of fall was assessed using the Timed Up and Go test. Data was entered into EpiData version 3.1 and exported to SPSS version 16 for analysis. Data analysis was performed using descriptive statistics, including frequency, percentage, mean, and standard deviation. The Chi-square test was used to assess the association between selected variables and risk of falls. Results: The findings of the study revealed that among 112 older adults, 61.6% of older adults had full function ability whereas 38.4% of older adults had moderate impairment of functional ability. Nearly half (43.8%) of older adults had a high risk of falls and 56.2% had no risk of falls. There was a significant association between risk of fall with age (p<0.001), gender (p<0.001), education (p<0.001), perceived health problems (p<0.003), history of falls (p=0.03), use of gait assistive devices (p<0.001), and functional ability (p<0.001). Conclusion: Considerable proportion of older adults have high risk of fall, age, gender, and functional ability tend to influence the risk of fall. Hence, screening programs should be conducted to identify those at risk and preventive programs should be launched to reduce falls and fall-related injuries among older adults.